COMPARATIVE EVALUATION OF FUSED DEPOSITION MODELING AND STEREOLITHOGRAPHY FOR 3D PRINTING OF PERSONALIZED ORAL DRUG DELIVERY SYSTEMS - THAKUR, HIMANSHU; PATEL, MEENAKSHI; MISTRY, BHARGAVI (International Journal of Applied Pharmaceutics, 2025)
Additive manufacturing, particularly three-dimensional printing (3DP), is rapidly transforming drug formulation and production in pharmaceutical sciences. This review focuses on two prominent 3DP techniques-fused deposition modeling (FDM) and stereolithography (SLA)-for the fabrication of solid oral dosage forms with controlled drug release. FDM offers advantages such as cost-effectiveness and compatibility with pharmaceutical-grade polymers, while SLA provides superior resolution and the ability to create complex, drug-loaded matrices. Despite these promising capabilities, challenges, including material limitations, regulatory hurdles, and the need for process optimization, hinder widespread clinical adoption. Recent advancements in material science and printing technology are beginning to address these issues, paving the way for more reliable and personalized drug delivery systems. This review summarizes the fundamental principles, key advantages, limitations, and ongoing innovations in FDM and SLA for pharmaceutical applications. Future directions include overcoming regulatory barriers, expanding material options, and integrating 3DP into mainstream personalized medicine.